(untitled) - Davenport, Thomas H. (Boston Massachusetts, 2014)
Big Data at Work covers all the bases: what big data means from a technical, consumer, and management perspective; what its opportunities and costs are; where it can have real business impact; and which aspects of this hot topic have been oversold.
Keywords: Kế hoạch kinh doanh,Business planning; Phương pháp thống kê,Statistical methods